TI_GERICHTE 16.2018.43 vom 10. September 2018 , Irricevibilità di un reclamo presentato contro un'autorizzazione ad agire - TI Tribunale d'appello (2018)
Irricevibilità di un reclamo presentato contro un'autorizzazione ad agire